2015
DOI: 10.1039/c5tb00990a
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-mimetic hydrogels promote human endothelial cell adhesion, migration and phenotypic maturation

Abstract: This work evaluates the response of human aortic endothelial cells (HAECs) to thromboresistant collagen-mimetic hydrogel coatings toward improving the biocompatibility of existing “off-the-shelf” small-caliber vascular grafts. Specifically, bioactive hydrogels – previously shown to support α1/α2 integrin-mediated cell adhesion but to resist platelet activation – were fabricated by combining poly(ethylene glycol) (PEG) with a 120 kDa, triple-helical collagen-mimetic protein(Scl2-2) containing the GFPGER adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(85 reference statements)
1
16
0
Order By: Relevance
“…The EC attachment attained is likely through the α1β1 and α2β1 integrins, which are well known to interact with GFPGER (Seo et al, 2010). This cell attachment is in agreement with the work of several groups, including ours (Chaouat et al, 2008;Munoz-Pinto et al, 2015;Anderson et al, 2019). GFPGER has been shown to support cell attachment and spreading on several surfaces, including a collagen-mimetic protein with GFPGER incorporated, Scl2 GFPGER , coated onto tissue culture plastic (Seo et al, 2010) and a Scl2 GFPGER incorporated PEG hydrogel (Cereceres et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The EC attachment attained is likely through the α1β1 and α2β1 integrins, which are well known to interact with GFPGER (Seo et al, 2010). This cell attachment is in agreement with the work of several groups, including ours (Chaouat et al, 2008;Munoz-Pinto et al, 2015;Anderson et al, 2019). GFPGER has been shown to support cell attachment and spreading on several surfaces, including a collagen-mimetic protein with GFPGER incorporated, Scl2 GFPGER , coated onto tissue culture plastic (Seo et al, 2010) and a Scl2 GFPGER incorporated PEG hydrogel (Cereceres et al, 2015).…”
Section: Discussionsupporting
confidence: 86%
“…Both of these sequences specifically recognize α1β1 and α2β1 integrins, which are known to bind ECs and both bind and upregulate platelet activation. The incorporation of GFPGER into materials has been shown to promote cell growth and, while in solution, the GFPGER sequence bound platelets but did not cause activation of the platelets (Munoz-Pinto et al, 2015). The effect on platelet attachment and aggregation due to a covalently linked GFPGER surface is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…85,168 Studies have also been performed on collagen mimics such as these peptide sequences that have more tailored integrin interactions. 49,112,139 These typically require coating studies or chemical crosslinking into another network, as they do not form networks on their own. 107 Collagen coat studies have demonstrated a difference in not only cell behaviors such as migration and proliferation as compared to TCPS but also differences in hemostatic regulation.…”
Section: Collagen-initiated Hemostatic Regulationmentioning
confidence: 99%
“…107 Collagen coat studies have demonstrated a difference in not only cell behaviors such as migration and proliferation as compared to TCPS but also differences in hemostatic regulation. 53,96,112,165 For example, endothelial cells cultured on collagen-coated ePTFE demonstrated lower levels of PGI 2 and tPA as compared to endothelial cells on an un-coated ePTFE control. 100 This would indicated a less thromboresistant phenotype, but this study did not analyze the production of complementary pro-thrombotic factors in the endothelial cells cultured on these substrates.…”
Section: Collagen-initiated Hemostatic Regulationmentioning
confidence: 99%
“…In one study, human aortic endothelial cells (HAECs) were cultured in the presence of either full-length Collagen or a Collagen-mimicking peptide SCL2–2 presented on PEG hydrogels. SCL2–2 is a Collagen mimicking protein presenting mainly Gly-Phe-Pro-Gly-Glu-Arg (GFPGER) as the integrin-binding domain [90]. HAECs adhered to full-length collagen had greater levels of NOS3 protein expression, greater gene expression levels of NOS3, Thrombomodulin and Selectin-E, and proliferation when compared to HAECs adhered to SCL2–2.…”
Section: Biomaterials As Tools To Model Vascular Morphogenesismentioning
confidence: 99%